Knowledge, Attitude, PPE Use in Production Workers and Work Accidents - Anugrah, M Pandu Fatwa; Sari, Rumita Ena; Wardiah, Rizalia; Aswin, Budi; Lanita, Usi (RRZ Scientific Publishing, 2024)
Work accidents are unexpected and unwanted events that can harm employees and companies. The production department has the highest risk of work accidents because it deals directly with machines and heavy equipment. This study aimed to determine the relationship between knowledge, attitudes, and use of Personal Protective Equipment (PPE) and work accidents in the production section of PT Cassia Co-Op, Sungai Penuh City. This type of research was analytic and observational, using a cross-sectional research design. The sampling technique was total sampling, with a total sample of workers. The researchers used questionnaires and observation sheets. Data analysis was performed using univariate and bivariate analyses using the chi-square test. There was a significant relationship between knowledge (p-value = 0,001) and attitudes (p-value = 0,029) with work accidents, and there was no significant relationship between the use of PPE and work accidents (p-value 0.156). Workplace agencies, such as PT Cassia Co-op, will likely employ K3 training to disrupt the causative chain of workplace accidents, which include harmful conditions, human errors, and unsafe acts. Thus, accidents and damage can be avoided.